Determination of Fatty Acid Composition, Cholesterol and Fat- soluble Vitamin Levels of Capoeta trutta, Luciobarbus mystaceus and Luciobarbus esocinus Caught from the Keban Dam Lake, Elaz??, Turkiye - Vanli, Enes; Harlioglu, Ayse Guel; Harlioglu, Muzaffer Mustafa; Kirmizikaya, Goerkem; Yilmaz, Oekkes (Central Fisheries Research Inst, 2023)
The fatty acid composition, cholesterol and fat-soluble vitamin levels in the muscle tissue of economically important freshwater fish Luciobarbus esocinus, Capoeta trutta and Luciobarbus mystaceus were investigated. The analysis of fatty acid methyl esters was carried out by gas chromatography, and cholesterol and fat-soluble vitamin amounts were determined by high-performance liquid chromatography (HPLC). Among polyunsaturated fatty acids (PUFA), eicosapentaenoic acid (EPA, C20:5n-3) was found to be higher in C. trutta (14.84%) compared to the other fish species, while the highest amount of docosahexanoic acid (DHA, C22:6n-3) was determined in L. mystaceus (20.43%). While the maximum amount of total n-3/n-6 PUFA ratio was determined for C. trutta with 4.64%, it was determined that the sum of EPA and DHA from n-3 series fatty acids was higher in C. trutta with 31.74%. When the fat-soluble vitamin and cholesterol levels of the species were compared, it was found that the difference between the amounts of delta-tocopherol, alpha-tocopherol, D3, K1, K2 and cholesterol did not differ between the species. In conclusion, L. esocinus, C. trutta and L. mystaceus living in the Keban Dam Lake are valuable food source in terms of fatty acids, vitamin and cholesterol. It is thought that the findings of this study is beneficial for researchers and fish consumers.
Keywords: Fish; Food quality; Eicosapentaenoic acid; Docosahexanoic acid; Vitamins